The socio-legal significance of decriminalising sex work in South Africa - Manuel, Stacey-Leigh (Department of Public Law, 2022)
This dissertation aims to interrogate the following research question: How would the decriminalisation of sex work model align with the South African human rights framework? The dissertation recommends the decriminalisation model of law reform, as it will fulfil public health goals and respect human rights. The study highlights the systemic patterns of abuse that sex workers in South Africa experience because of the criminalisation of sex work. In response to the research question, an analysis of the impact of criminalisation on sex worker's human rights is offered together with a description and analysis of existing legislative models such as the legalisation model (adopted in the Netherlands), partial criminalisation model (also known as the ‘end-demand' model, which is enforced in Sweden) and the decriminalisation model (applied in New Zealand and Australia), as well as how the aforementioned models might benefit sex workers and the broader society. In addition, the dissertation addresses the current legal position and jurisprudence on sex work in South Africa. The impact of the criminal law on sex workers and general society is discussed and the current untenable position created by outdated legislation is highlighted. An analysis of the current legal framework in South Africa that prohibits sex work is provided, and the impact of the current legal framework on sex worker's constitutional human rights is examined. The case precedents on sex worker human rights in South Africa and the existing legal models, as mentioned above, on sex work are also analysed. A consideration of South Africa's compliance obligations under international and regional human rights treaties and the South African Constitution, as well as the statutory approaches adopted in New Zealand, Australia and the Netherlands are further explored. The intended outcomes of this dissertation are: a) To illustrate that the decriminalisation model of sex work is compatible with the human rights framework in South Africa; and b) To provide a basis for a proposal for an appropriate legal model for South African policy makers, tasked with formulating and implementing a statutory framework that recognises and protects the human rights of sex workers in South Africa.